(untitled) (SAARC Journal of Agriculture, 2016)
A field experiment was done for two consecutive years from 2010-11 to 2011-12 with two varieties of wheat (DBW 17 and DPW 621-50) and ten treatments of fertilizer, involving NPK, FYM and micronutrient, with an objective to maximize the crop yield. Results showed that variety DBW 17 recorded significantly higher grain yield (4.93 %), straw yield (6.31%) and HI (1.12%) as compared to DPW 621-50. There was no significant difference in yield attributes between two varieties. Application of 150 % recommended NPK fertilizers produced the maximum grain yield (6.10 t ha-1), which was 7.7 % higher over the 100% NPK fertilizers, followed by 15 t ha-1 FYM application along with 150 (5.98 t ha-1) and 125 % (5.96 t ha-1) NPK application. There had no significant effect of micronutrients (Zn, Cu, Fe & Mn) on wheat yield indicating that the soil was not deficient in those micronutrients. A significant variation was observed between two years in respect of yield and yield attributes, higher performances being recorded in 2011-12. Crop lodging was observed, with a maximum lodging of 26.4 % causing a yield reduction of up to 9.9 %. Agronomic efficiency was the maximum (13.64 kg grain kg-1 fertilizer) with the recommended rate of fertilizers and it decreased with increasing rates. Addition of FYM didnt increase the agronomic efficiency due to inclusion of 75 kg N contribution from 15 t ha-1 of FYM. SAARC J. Agri., 14(1): 103-110 (2016)